Evaluasi dan Perancangan Model Bisnis Kripik Bujangan dengan Business Model Canvas - Zahira, Alda; Hasun, Farda; Rendra, Meldi (Universitas Muhammadiyah Sorong, 2025)
Kripik Bujangan is one of the MSMEs from Bandung City which has been established since 2022 and sells various types of spicy chips typical of West Java. Kripik Bujangan has a sales target of 2000 packages for each month, but sales show a downward trend so that it cannot meet the target. The root of the problem that has been identified is from the aspects of people, process, product, promotion, and place. One way that can be done to overcome these problems is to evaluate and design a proposed business model for Kripik Bujangan using the Business Model Canvas framework. Some data required for this research are current business model data, customer profile data, and business model environment data. Evaluation of the current business model was carried out using 7 questions analysis and SWOT analysis. SWOT analysis is carried out for the entire canvas (big picture level), then an assessment is carried out by Kripik Bujangan. From the results of the SWOT analysis, a strategy design using the TOWS matrix was carried out to improve the company's business model which was then translated into the proposed Business Model Canvas. Some of the proposed improvements include expanding the reach of individual customers, adding marketplace channels (Shopee) and Indomaret in the Jakarta area, increasing the variety of flavors and product sizes, adding workers and adding to business support equipment. Furthermore, a financial simulation was conducted by calculating the estimated revenue and additional costs based on the proposed business model changes. The proposed business model changes are feasible to implement if sales increase by 10%.